Intervening factors for the execution of the budget for donations and transfers at the Lambayeque Regional Hospital - Perú - Ordemar-Vásquez, Percy Dante (2020)
Objective: To determine the factors involved in the implementation of the donation and transfer budget at the Lambayeque Regional Hospital. Material and Methods: Not experimental, descriptive, quantitative approach, cross-section, during 2019. Population and sample was 57 collaborators, non-probabilistic sampling, for convenience. The Oria instrument was divided into : institutional factor, political factor, organizational factor and personal factor, reliability by Cronbach alpha; in addition, the Kolmogorov-Sminorv test was used for the normality of the population; and for statistical significance the descriptive analysis. Findings: the average intervention level of 3,444 for the variable factors involved being the most outstanding factor the Politician (average 3,7222) and the most outstanding item (84%) referring to the paperwork of the administrative processes, delays the budgetary execution of expenses. Conclusions: There is a medium level of intervention of the factors involved in the execution of the donation and transfer budget of the Lambayeque Regional Hospital.